Design and thermal analysis of coated and uncoated exhaust manifold. Issue 2 (28th January 2020) - Valarmathi, T. N.; Sekar, S.; Purusothaman, M.; Saravanan, J.; Balan, K. N.; Sekar, S. D.; Mothilal, T.
ABSTRACT: The exhaust manifold is used to collect and deliver waste toxic gases through a single pipe. During this process, the exhaust manifold suffers from the thermal stresses causes blowholes on the manifold. In this study, to prevent the defects of the exhaust manifold, a different coating is applied using ceramic materials. The 3D models of the coated and uncoated manifold have been developed using CATIA and analysed using thermal analysis by ANSYS software using finite element methodology.